Digitalizing Goods Declaration: Performance Analysis of the Bureau of Customs Portal in Key Philippine Ports - Aldrin Alvarez; Emmanuel Dotong; Rose Daphne Oller (Inclusive Society and Sustainability Studies, 2026)
This study assesses the performance of the Bureau of Customs (BOC) portal at major Philippine ports under the “zero contact” policy mandated by Customs Memorandum Order 8-2020, focusing on efficiency, accuracy, and regulatory compliance in Goods Declaration (GD) processing. A quantitative-descriptive design was employed using surveys and secondary time-series data from BOC records. Respondents included licensed customs brokers and declarants at the Port of Manila and the Manila International Container Port, for a total of 363 participants. Guided by the Technology Acceptance Model (TAM), descriptive statistics and paired-sample t-tests were used to compare pre- and post-implementation performance. Findings reveal significant reductions in GD processing time (3.80 to 3.04 days), documentation verification (13.91 to 4.76 hours), and clearance and release (3.74 to 2.91 days). However, system downtime averaging 7.04 hours per month delays approximately 240 GDs per incident and reduces processing efficiency by 0.99%. The GD error rate stands at 4.33%, with corrections averaging 132.43 days; audit trail features are effective but only moderately enhance dispute resolution. Common user errors include typographical mistakes and incorrect attachments, while technical support remains a major bottleneck (average resolution time: 138.65 hours; resolution rate: 0.79%). The study recommends strengthening technical support and ticketing systems, upgrading infrastructure, streamlining error correction, and enhancing audit trails and feedback mechanisms to align the BOC portal with international customs digitalization standards.